The effect of rubber type and rubber functionality on the morphological and mechanical properties of rubber-toughened polyamide 6/polypropylene nanocomposites - Wahit, Mat Uzir; Hassan, Azman; Mohd. Ishak, Zainal Ariffin; Rahmat, Abdul Razak; Othman, Norhayani (Nature Publishing Group, 2006)
Rubber toughened polyamide 6/polypropylene (PA6/PP) nanocomposites containing 4 wt % of organophilic modified montmorilonite (OMMT) were produced by melt compounding followed by injection moulding. Four different types of elastomer were incorporated into the blends as a toughener, i.e., ethylene-octene elastomer (POE), ethylene-propylene elastomer (EPR), maleated POE (POEgMAH) and maleated EPR (EPRgMAH). The influences of maleating on the interfacial adhesion and mechanical properties of the nanocomposites were investigated in term of mechanical testing, the X-ray diffraction (XRD) and scanning electron microscope (SEM) observation. The results showed that modulus and strength of the nanocomposites was not significantly affected by types of elastomer and their functionality. However, the toughness of the nanocomposites toughened by maleated elastomer was higher than the unmaleated elastomer. The SEM observation revealed that rubber functionality reduces the elastomer particle size in the PA6/PP matrix due to the in situ formation of graft copolymer between maleated elastomer and PA6 during melt processing. XRD revealed that the type of elastomer and functionality did not affect the dispersion of the organoclay in the system.